GERAKAN DAKWAH PADA ORGANISASI NAHDLATUL ULAMA - Prabowo, Eko (Qaulan Baligha: Jurnal Ilmu Manajemen Dakwah, 2025)
Nahdlatul Ulama is a socio-religious organization. Founded by the ulama of the 1926 Islamic boarding school in Surabaya, K.H. Hasyim Asy'ari, the founder of nahdlatul ulama, a charismatic kiyai. Through a deeper understanding of the Nahdlatul Ulama da'wah movement, we can explore NU's significant contribution to the formation of the face of Islam in Indonesia and its important role in maintaining inter-religious harmony in the country. The background of the establishment of NU is closely related to the development of religious and political thought in the Islamic world at that time. This study explains the da'wah movement in the organization of nahdlatul ulama which explains how the organization of nahdatul ulama this study uses literature studies taken from various research sources.